55.1k views
3 votes
-3y + 14 + y = 12 how do i solve this combining like terms

2 Answers

1 vote

Answer:

-2(1) + 14 = 12

Explanation:

Combine -3y and y which would be -2y + 14 = 12 you just have to fill in the variable as far as i know would be 1 because 1 times -2 is -2 and so -2+14=12

User Phss
by
4.9k points
5 votes

Answer: y=1

Explanation:

combining like terms is like adding or subtracting but with a variable for example -3y and y have the same variable so you can combine them. -3y+y is -2y so -2y+14=12 subtracting 14 from both sides to isolate y you get -2y=-2 divide by -2 and you get y=1

User Dmitriy Snitko
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.